THE SPECIES JURINEA ZAKIROVII, HELICHRYSUM NURATAVICUM AND OXYTROPIS PSEUDOROSEA WHOSE NATURAL POPULATIONS ARE EXPANDING IN THE NUROTA BOTANICAL-GEOGRAPHICAL DISTRICT (International Conference on Scientific Research in Natural and Social Sciences, 2025)
The article presents information about the species Jurinea zakirovii, Helichrysum nuratavicum and Oxytropis pseudorosea whose natural populations are expanding in the Nurota botanical-geographical district.